Parameterization, analysis, and risk management in a comprehensive management system with emphasis on energy and performance (ISO 50001: 2018) (2020)
The future of business development relies on the effective management of risks, opportunities, and energy and water resources. Here, we evaluate the application of best practices to identify, analyze, address, monitor, and control risks and opportunities (R/O) according to ISO 31000 and 50000. Furthermore, we shed light on tools, templates, ISO guides, and international documents that contribute to classifying, identifying, formulating control, and managing R/O parameterization in a comprehensive management system model, namely CMS QHSE3+, which consists of quality (Q), health and safety (HS), environmental management (E), energy efficiency (E2), and other risk components (+) that include comprehensive biosecurity and biosafety. By focusing on the deployment of R/O-based thinking (ROBT) at strategic and operational levels, we show vulnerability reduction in CMS QHSE3+ by managing energy, efficiency, and sustainability.